Managing the iceberg of knowledge: Organizational memory in search of excellence - Sharuddin, Noraziah (2001)
Organizations have valuable assets in the form of formal and informal knowledge, which are dispersed throughout the organization. Knowledge is also available within the circles of their knowledge workers but this valuable intellectual asset usually lives only in the collective human memory and thus is being poorly preserved and managed or otherwise just being ignored. There is a need to gather explicit and persistent representation of knowledge dispersed around groups of people in the organization, which can be used to improve the activities of the organization. This paper will address the importance of organizational memory and focus specifically the knowledge management initiatives by Perpustakaan Sultanah Zanariah in support of the creation of the University Organizational Memory.